Feed efficiency in the beef industry - Hill, Rodney A. (Wiley-Blackwell, 2012)
"Feed efficiency is increasingly seen as an important factor in both the economic viability and environmental sustainability of cattle production. This book provides beef industry professionals and researchers with a thorough yet concise overview of feed efficiency research. Coverage includes efficient production in a wide range of systems and environments, with topics ranging from economic evaluation to the physiological and genetic basis of feed efficiency. The book also looks at how a fuller understanding of feed efficiency is leading to new selective breeding efforts to develop more efficient cattle"--